TMIC-13. EFFICACY OF RETINOIC ACID IN REVERSING IMMUNE EVASION IN IDH MUTANT GLIOMAS. (5th November 2018) - Rao, Aparna; Zhang, Xiaoran; Kim, Jason; Kim, Youngmi; Holland, Eric; Amankulor, Nduka
Abstract: BACKGROUND: Most diffuse gliomas are characterized by mutations in isocitrate dehydrogenase 1 or 2 (IDH1/2). Among its many effects, these mutations drive specific epigenetic programs that result in tumor cell intrinsic resistance to innate lymphoid cells. Here, we define a central role for retinoic acid signaling in mediating immune resistance to innate anti-tumor immunity in IDH mutant tumors. IDH mutations in gliomas suppress retinoic acid signaling through transcriptional repression of Retinol Binding Protein 1 (RBP1), a key chaperone protein in retinoic acid biosynthesis. Loss of retinoic acid signaling results in diminished expression of retinoic-acid-responsive genes, including activating NKG2D ligands ULBP1 and ULBP3 and results in resistance to natural killer (NK cells). METHODS: We evaluated the efficacy of all-trans retinoic acid (ATRA) as a therapeutic adjuvant for IDH mutant gliomas. In a series of in vitro and in vivo experiments, we assessed the ability of ATRA to increase NKG2D ligand expression in IDH mutant cells, and its ability to increase NK-mediated recognition and killing. We also looked at the impact of ATRA on the tumor immune microenvironment and its underlying mechanisms RESULTS: ATRA treatment led to increased recognition and killing of IDH mutant glioma cells by NK cells, by increasing NKG2D ligand expression. In vivo, ATRA treatment led to significantly slower tumor growth in IDH mutant tumor-bearing mice. Importantly, we made the unexpected finding that restoration of retinoic acid signaling dramatically reshapes the landscape of the immune microenvironment by permitting infiltration of NK cells and CD8 T cells in a manner dependent on the chemokine CCL2. CONCLUSIONS: Retinoic acid therapy using ATRA results in marked suppression of IDH mutant glioma tumor growth in an NK cell-dependent fashion in preclinical animal models of glioma. These findings have important therapeutic implications for the treatment of IDH mutant diffuse glioma.